Konsumsi dalam Metafora Maqāṣid Al-Syarī‘ah - Dedi Mardianto; Irwan Misbach (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study discusses the phenomenon of increasing consumptive behavior among Muslim communities due to the influence of social media, technology, and e-commerce. This behavior is considered contrary to Islamic teachings that emphasize balance, simplicity, and social responsibility. Therefore, this research aims to formulate the concept of Islamic consumption that not only fulfills physical needs, but also considers spiritual values, ethics, and social justice. Using a qualitative approach through literature study, this research examines consumption principles in Islam such as halal-thayyib, maqāṣid al-syarī'ah, and ethical rationality as an alternative to conventional consumption that is materialistic. The results show that consumption in Islam is part of worship that includes spiritual, social, and environmental dimensions. Islamic consumption encourages frugal, selective, and responsible behavior, and strengthens social solidarity through zakat and alms. This research produces an integrated Islamic consumption framework that can serve as a guideline for Muslim consumers, policy makers, and da'wah institutions in building a more ethical, sustainable, and Islamic-compliant consumption lifestyle in the modern era.